Persepsi dan Self-Efficacy terhadap Perilaku STBM Pilar 1 di Daerah Lahan Kering Kepulauan - Junias, Marylin S.; Benu, Yuliana Marlyn; Toy, Sarci M.; Sudarmadji, Claudya S. Virlynriana; Lona, Atarini A. (Journal of Telenursing (JOTING), 2024)
This study focuses on The Self-Efficacy and Community Perspectives Regarding STBM Pillar 1, specifically the practice of defecation cessation, in Taebenu district, Kupang Regency, East Nusa Tenggara. The research methodology used is qualitative, utilizing interpretative phenomenological analysis (IPA). Ten individuals were selected as informants as they play a significant role in the community's empowerment process related to sanitation. The data was collected through interviews guided by interview protocols. The outcomes of these interviews and focus Group Discussions (FGDS) were transcribed word-for-word and analyzed thematically. The research findings revealed that the majority of the informants shared latrines with their neighbors. However, they expressed feeling uneasy and rushed while using these facilities. They had to coordinate with their neighbors regarding timing, which often led to defecating in the forest. Additionally, children frequently used their neighbor's latrines. Despite financial constraints, the informants had high self-efficacy and believed that they could afford private toilets. They were motivated to change their behavior regarding defecation cessation to promote good health, maintain cleanliness, avoid embarrassment from neighbors, and protect their children's health. Keywords: Self-Efficacy, Defecation, STBM.